Oil yield and composition of young Santalum yasi in Fiji and Tonga. Issue 4 (1st October 2020) - Bush, D.; Brophy, J.; Bolatolu, W.; Dutt, S.; Hamani, S.; Doran, J.; Thomson, L.
ABSTRACT: Santalum yasi, a sandalwood native to Fiji and Tonga, is a tree crop of significant economic potential for these countries. Development of a plantation industry underpinned by a breeding program is a high priority for industry development. Gathering information on heartwood development, oil yield and oil composition is a critical step for the domestication and tree breeding of the species. Oil yield and composition were determined for 86 Santalum core samples using gas chromatography and combined gas chromatography/mass spectrometry. Most (67) cores were from the lower boles of individual trees of S. yasi, with smaller samples of S. album and S. album × S. yasi, both of which are also commonly grown in Fiji and Tonga, and S. austrocaledonicum was included for comparison. Although the ages of the trees were unknown, they are likely to have been between 10 and 20 years. Relationships among traits, including solvent-extracted oil yield, oil composition, lower bole diameters under and over bark, and heartwood diameter, were examined. Yield was highly variable (0.05–11.8%) and only weakly correlated with underbark diameter at 30 cm above ground. Oil yield and percent composition of santalol oil components were strongly positively correlated. For those trees with oil yields >1% w/w, the oil composition was generally favourable relative to the international standard for S. album oil, with large proportions of santalols, particularly β -santalol. The study confirms that both harvesting and selection for genetic improvement of S. yasi trees younger than 20 years old are likely to be suboptimal, with unreliable heartwood and oil development. Further study of heartwood and oil development, both within individual trees and among genotypes in common-garden trials with known genetics and controlled environments and hosts, is a high priority. The development of an international standard for S. yasi, supporting the growth of a niche market for the product, is also recommended.